Acute in-patient treatment for adults with learning disabilities and mental health problems in a specialised admission unit. - Trower T; Treadwell L; Bhaumik S (British Journal of Developmental Disabilities, 1998)
Psychiatric and behaviour disorders are common in adults with learning disabilities. For some a period of in-patient assessment/management becomes necessary from time to time. Uncertainty remains as to whether such admissions should be to specialist in-patient units or to generic mental health in-patient facilities. In Leicestershire (population 890,000) a 12 bedded specialised admission unit was opened in 1992 for adults with learning disabilities requiring admission for the assessment and treatment of additional psychiatric or behavioural problems. The use of this unit over the two year period August 1993 - July 1995 was reviewed retrospectively by the use of clinical case notes. There had been a total of 113 new admissions, accounted for by 80 individuals. The findings suggest that the unit provides an in-patient service for individuals with learning disability throughout the disability spectrum. Admissions were for the assessment and treatment of psychiatric disorders, behaviour disorders and occasionally epilepsy. Most individuals were successfully treated within 6-7 weeks and discharged back to the residence from which they were admitted. However, a small group (four individuals) were identified who had prolonged admissions (over one year).